Assessing the Design Preferences of Ageing Residents in Malaysian Elderly Care Homes - Alice Sabrina Ismail , Roshida Abdul Majid , Fadhlina Ahmad Taufik , Norshahida Azili , Muhammad Nor Haziq Zamry (International Journal of Advanced Science and Technology, 2020)
Many of the existing elderly care homes in Malaysia are lacking in terms of design consideration to fulfil the requirements of seniors as they age further. Past literature on elderly care homes nevertheless, only much focuses on the aspect of management and services, social health care program and facilities as well as living arrangements suitability for the elderly residing in the elderly care homes. None, however, attempts on discussing and determining the best practice guidance in terms of design preferences to fulfill ageing resident’s needs. This paper discusses on the design issues and challenges in current elderly care homes followed by examination through the appearance and configuration of both the exterior and interior of the existing home care. This is vital to establish appropriate design strategies in terms of architectural design layout involving the quality of home environment in terms of living, emotional and facilities comfort whereas maintaining the existing cultural values. This study adopts mixed methodology strategy framed by the interpretivism paradigm approach in which all qualitative data were analyzed using hermeneutics and coding whilst the quantitative data were examined using SPSS technique. Findings indicate that ageing residents much prefer home design with proper contextual responsiveness, appropriate building envelope, suitable site planning with comfortable unit dwellings space as well as suitable form making qualities. This paper is of benefit for future designers, builders, developers and related authorities to improve the design quality of elderly housing in Malaysia in the aspect of physical planning guidelines.